Videogames and art - Clarke, Andy, ....-; Mitchell, Grethe, ....- (Bristol : Intellect, 2007)
From Madden NFL 2007 to Grand Theft Auto: Vice City, videogames are firmly enmeshed in modern culture. Acknowledging the increasing cultural impact of this rapidly changing industry, Videogames and Art is one of the first books devoted to the study of videogame art, featuring in-depth essays that offer an unparalleled overview of the field. The distinguished contributors range broadly over this vast intellectual terrain, positioning videogame art as a crucial interdisciplinary mix of digital technologies and the traditions of pictorial art. They examine machinima and game console artwork, politically oriented videogame art, and the production of digital art; they also interview prominent videogame artists about their work. Rounding out Videogames and Art is a critique of the commercial videogame industry comprising several critical essays on the current quality and originality of videogames. An essential volume for our digital age, Videogames and Art will be a fascinating read for players, fans, skeptics, and scholars alike.